THE EFFECT OF EDUCATION, WORK EXPERIENCE AND CERTIFICATION OF COMPETENCE ON WORK SKILL (STUDY OF LITERATURE REVIEW HUMAN RESOURCES) - Ding Chong (Dinasti Publisher, 2022)
The Literature Review article on the Effect of Education, Work Experience and Competency Certification on Work Skills (Study Literature Review of Human Resources) is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Education has an effect on Work Skills; 2) Work Experience has an effect on Work Skills; and 3) Competency Certification has an effect on Work Skills. Apart from these 3 exogenous variables that affect the endogenous variable Work Skills, there are still many other factors including the variables of Motivation, Communication and Teamwork.